Pengaruh Pemasaran Digital dan Suasana Toko Terhadap Minat Beli di Kedai Kopi S - Khalifachri Albi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2020)
This study aims to analyze the influence of digital marketing and store atmosphere on buying an interest in Kedai Kopi S. Sources of data were obtained from observations on Kedai Kopi S’s customers in May 2019. The method used was the descriptive method by distributing questionnaires through Google Form, then processed using IBM SPSS Statistics application. Based on 105 respondents who have come to Kedai Kopi S and have accessed the Kedai Kopi S Instagram. The results show that digital marketing and store atmosphere affect buying interest. The accepted hypothesis was decided based on the results of the t value analysis. It can be concluded that Kedai Kopi S needs to improve promotion through social media so that consumers can consider more about coming to Kedai Kopi S.